Foot care knowledge and self-care practices among diabetic patients in Penang: a primary care study - Jing, Ong Jue; Azmil, Siti Sarah; Sean, Kang Cheow; Fuen, Lim Siew; Choo, Ooi Gaik; Patel, Avni; Mawardi, Maliza (Malaysian Medical Association, 2022)
Introduction: In Malaysia, the prevalence of diabetes mellitus has been increasing annually, currently affecting 18.3% of the population. Diabetic foot ulcer, a common complication of diabetes, is associated with high morbidity and mortality, consequently increasing health care expenditure. A previous study showed that foot care knowledge and foot self-care practices help to reduce the development of ulcers.1,2 This study aims to identify the level of foot care knowledge and self-care practices among diabetic patients in the primary care setting. Objective: This study was to determine the level of foot care knowledge and foot self-care practices among diabetic patients in the primary care setting in Penang Island and its determinants and the correlation between level of foot care knowledge and self-care practices among diabetic patients. Material and Methods: A cross sectional study was performed on 311 diabetic patients who were registered to two government health clinics in Penang. Information regarding respondents’ demographic status, foot care knowledge, and foot self-care practices were gathered using a self-administered questionnaire. Data were analysed using the Statistical Package for the Social Sciences (SPSS) 22. The Mann–Whitney U test and Kruskal–Wallis test were applied to the analysis. Multiple linear regression was performed to identify the determinants. Correlation between knowledge and self-care practice was determined using the linear regression model. Results: One hundred and sixty-five (53.1%) respondents achieved good knowledge scores and 196 respondents (63%) achieved good self-care practice scores. The median age of respondents was 61 years, who were mostly females (56.6%), Malays (41.2%), and unemployed (48.6%). Median HbA1c level was 7.5%, and 42.8% of respondents had diabetes for 5 to 10 years. Lowest scores for knowledge and self-care practices were observed in foot skin care questions. Formal foot care education was found to be a significant predictor of foot care knowledge (p<0.05, 95% CI −1.102, −0.098). Foot care knowledge was significantly and positively correlated with foot self-care practices (p<0.001, 95% CI 0.548, 0.727). Conclusion: Foot care knowledge has significant positive correlation with foot self-care practices. Empowering diabetic patients with foot care knowledge may lead to significantly better foot self-care practices.